Pulmonary Hypertension and Weaning - Ceren Gunt; Nedim Çekmen (Türk Yoğun Bakim Derneği Dergisi, 2016)
Pulmonary hypertension is a patophysiologic state of pulmonary circulation that mean pulmonary arterial pressure is measured as equal to or greater than 25 mmHg at rest via right heart cateterization. Although this disease is very common in intensive care unit (ICU) patients and determines the clinical course, the diagnoses cannot be made or cannot be noticed typically. Pulmonary hypertension, due to being the cause of heart failure and progressive vascular remodelling in lung, leads to an increase in respiratory load. This result effects weaning process directly in these patients. Pulmonary hypertension which is not yet diagnosed should be considered in ICU who are in difficult or prolonged weaning group. For a successful in these patients, an optimal fluid management and avoiding factors trigerring increase in pulmonary vascular resistance (hypoxi, hypercarbia, high positive end-expiratory pressure, asidosis and hypothermia) are essential.